CFTC adopts amendments to position limit aggregation rules. Issue 2 (3rd July 2017) - Bruynes, J.P.; Daniel, Jason; Walker, Libbie
Abstract : Purpose: To explain the final position limit aggregation rules and exemptions pertaining to derivative positions in nine agricultural commodities adopted by the Commodity Futures Trading Commission on December 5, 2016 and effective February 14, 2017, the notice filing deadline with respect to which was extended by the CFTC by limited time no-action relief until August 14, 2017. Design/methodology/approach: Explains the position limit aggregation rules and exemptions pertaining to equity interests in owned entities, ownership or equity interests in pooled accounts or positions, positions of an "eligible entity" in connection with client positions carried by an "independent account controller, " positions held by futures commission merchants (FCMs) in discretionary accounts or customer trading program accounts, equity interests of underwriters based on unsold allotments of securities in distributions, broker-dealers if the equity interest is acquired in the normal course of business and positions for which information cannot be collected without risk of violating a law. Findings: Unless an exemption from aggregation is available, all positions in accounts for which any person controls the trading or holds a 10 per cent or greater ownership or equity interest must be aggregated with positions held, and trading done, by such person. The final rule adds several new exemptions, including for persons with a 10 per cent or greater ownership or equity interest in an entity so long as certain conditions establishing independence are met. The final rule requires notice filing to take advantage of most exemptions from aggregation. Originality/value: Practical guidance from experienced lawyers specializing in securities, funds, and investment management.